Development Cooperation - Evaluation and New Approaches - Heinz Ahrens (Duncker & Humblot, 2005)
This volume represents some of the Proceedings of the Annual Meeting of the Research Committee on Development Economics (Ausschuss für Entwicklungsländer) of the German Economic Association (Verein für Socialpolitik) held in Cologne, Germany, in July 2004. The meeting focused on the effectiveness of, and new approaches in, development cooperation. Both issues have become increasingly important in recent years in view of the declining volume of budget funds allocated to development cooperation. – The papers discussing the effectiveness of foreign aid shed new light on the issue at a crucial moment where economists have begun to question the recent consensus that the productivity of aid mainly depends on the recipient country's policy environment. As far as the contributions dealing with new approaches in development cooperation are concerned, these are centred on a closer integration of the private sector, by joint action with so-called lead firms in production networks on the one hand, and the mobilization of additional financial resources from international capital markets for bilateral development cooperation, on the other. The authors also make suggestions concerning critical aspects relevant for implementation. The last part of this volume is dedicated to an assessment of low-income countries' pension schemes based on the human capital approach
Keywords: 330; Wirtschaftspolitik; Internationale Wirtschaftszusammenarbeit; Entwicklungspolitische Zusammenarbeit; Wirtschaftshilfe; Finanzielle Auslandshilfe; Wirtschaftliche Entwicklung; Chile; Malaysia; Effizienz/Effektivität; Privatwirtschaft; Finanzmarkt; Bilaterale Auslandshilfe; Armutsbekämpfung; Humankapital; Entwicklungsökonomie; Entwicklungszusammenarbeit; Rentensystem; Entwicklungshilfe; Wirkungsanalyse; Welt; Entwicklungsländer